EFFECT OF WORK DEMANDS ON BURNOUT THROUGH JOB RESOURCES IN SIDOARJO - Fachrudy Asj’ari; Firanti Reza Yuliarno; I Made Bagus D; Erwan Aristyanto (Jurnal Ekonomi, 2022)
This study aims to examine and analyze the effect of work demands on burnout through job resources for teachers at MTs Al-Ihsan Krian Foundation in Sidoarjo. The teacher is an important role in the world of education because the teacher has a fairly large educational role in the success of an educational institution. The method used in this study is using quantitative research methods with the samples used in this study as many as 50 respondent using a questionnaire method with a rating scale using a likert scale. The sampling technique used is a non-probability sampling technique with a saturated sample. The data analysis technique used is using partial least square (PLS) with statistical analysis test tools using SmartPLS 3 software. The results of the study show that : 1) work demands have a significant and positive effect on job resources for teacher at Al-Ihsan Krian foundation MTs in Sidoarjo. 2) work demands have a significant and positive effect on burnout teacher at the Al-Ihsan Krian Foundation MTs in Sidoarjo. 3) job resources have no significant and negative effect on burnout teacher at the Al-Ihsan Krian Foundation MTs in Sidoarjo.